ANALISIS KELAYAKAN USAHA SARI BUAH BELIMBING DI KOTA BLITAR - Jabal Tarik Ibrahim; Ary Bakhtiar (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Star fruit cultivation business has become one of the economic supports for people from Karangsari, Blitar. Number of star fruit production continuing to increase by years in which it becomes the background of people from Karangsari in making innovative products from star fruit star fruit. This study aims to determine the feasibility of star fruit juice business. The research was conducted at “Cemara Sari”, Self-Finance Agricultural Training Center and Rural (P4S), in Karangsari, Blitar. The location selection used purposive sampling technique by considering that Blitar is the center of fruit star fruit development in East Java. The allocation time for the study start from August to September, 2014. Star fruit extract business is considered financially feasible. It can be seen from the value of NPV by Rp 45.728.311, -; Net B / C = 4.09; gross B / C = 1.3; profitability = 7.3; and IRR by 89.13% Keywords: star fruit, star fruit extract, business feasibility.